Coherence analysis differentiates between cortical myoclonic tremor and essential tremor. - van Rootselaar, A; Maurits, N; Koelman, J; van der Hoeven, J; Bour, L; Leenders, K; Brown, P; Tijssen, M (2006)
Familial cortical myoclonic tremor with epilepsy (FCMTE) is characterized by a distal kinetic tremor, infrequent epileptic attacks, and autosomal dominant inheritance. The tremor is thought to originate from the motor cortex. In our patient group, a premovement cortical spike could not be established on electroencephalogram (EEG) back-averaging. Corticomuscular and intermuscular coherence analysis can demonstrate a cortical common drive to muscles. We carried out coherence analysis of electromyography (EMG) of forearm muscles and EEG of contralateral motor cortex in 7 FCMTE patients, 8 essential tremor (ET) patients, and 7 healthy controls. Results showed strong cortico- and intermuscular coherence in the 8- to 30-Hz range in the FCMTE patients, with EEG preceding EMG. Healthy controls and ET patients showed normal weak coherence around 20 Hz. The ET patients showed some additional coherence at tremor frequency (6 Hz), probably the result of sensory information flowing back to the sensorimotor cortex. These findings point to a pathological cortical drive in FCMTE patients leading to tremulous movements. Coherence analysis is an easy and useful method to differentiate FCMTE from ET. Coherence analysis is helpful when investigating a cortical common drive in cortical tremor and other movement disorders.